The Increasing Sustainability Threats to Community Pharmacies in Low- and Middle-Income Countries: Insurance Coverage Barriers and Policy Recommendations - Okoro, Roland Nnaemeka (Journal of Pharmacy Practice and Community Medicine)
Because of the nature of their practice and location, community pharmacies subject their owners and employees to heightened risk from theft, fire, and malpractice, among other threats. As a result, liability insurance is required for community pharmacies and their personnel. This paper describes the vulnerability of community pharmacies and their employees to liabilities, as well as the insurance options and benefits they offer. Finally, challenges to insurance policy uptake by community pharmacies in low- and middleincome countries were identified, and recommendations to help promote insurance uptake were made.
Keywords: Community pharmacy; Insurance policies; Low- and middle- income countries; Pharmacists; Threat